A death in summer : a novel - Black, Benjamin, 1945- (Henry Holt and Co., 2011)
When newspaper magnate Richard Jewell is found dead at his country estate, clutching a shotgun in his lifeless hands, few see his demise as cause for sorrow. But before long Doctor Quirke and Inspector Hackett realize that, rather than the suspected suicide, "Diamond Dick" has in fact been murdered.